Analysis of the prevalence, etiology, and risk factors of stillbirth from a teaching institute of North Eastern India- a retrospective study - Das, Rituparna; Sharma, Nalini; Lyngdoh, Bifica S.; Panda, Subrat; Saha, Anusmita; Shullai, Wansalan K.; De, Biswajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Stillbirth rate is considered a health index. The worldwide stillbirth rate is 18.4/1000 total birth. This study was aimed to evaluate the prevalence and risk factors of intrauterine fetal death in pregnant women in one of the teaching centers in Northeastern India. Methods: This was a retrospective study. All cases of intrauterine fetal death admitted in the department of obstetrics gynecology of our institute were included over two and half years. Information was gathered from the medical records of the patients and data were analyzed. Results: During two and half year’s period, the total number of deliveries was 2696 and the total numbers of stillbirths were 96, hence the stillbirth rate was 35.6/1000. 93 (96.87%) were antenatal stillbirths and 3 (3.12%) were intrapartum stillbirths. 82 (85.41%) women were unbooked. 85 (90.4%) belonged to low socioeconomic status. 67 (69.79%) were preterm. Maximum 39 (40.62%) belonged to 28-35 weeks of gestational age. The most common cause of Intrauterine death (IUD) was antepartum hemorrhage (17.7%). 14 (14.5%) were abruption and 3 were placenta previa. The second most common cause (14.5%) was the hypertensive disorder of pregnancy. Conclusions: The stillbirth rate in our institute is higher than the national average. The most common causes of IUD were antepartum hemorrhage, preeclampsia, prematurity, and malpresentation which can be diagnosed and managed by increasing uptake of antenatal care which will lead to timely identification and proper management of maternal and fetal complications eventually reducing the preventable stillbirths.